Membangun Pojok Baca di PAUD Lestari Desa Cendil - Asena, Alvin; Mahendra, Joni (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
In the context of improving the quality of education, developing literacy is an absolute must at all levels of education. Literacy activities are currently a priority in the development of the world of education, especially in the aspects of writing and reading. We can find out information by reading, and we can broaden our insight and think critically. Without reading, we cannot know what is happening in the world, and we cannot know the knowledge that exists in the world, therefore reading is important in knowledge and teaching and learning. The development of children's interest in reading and reading ability is currently very worrying (2) The research uses qualitative research with a descriptive approach. Qualitative research is understood as a series of research processes that are designed in such a way as to examine conditions in the field objectively and truly (3) creating a reading corner is one of the work programs that we will create and develop. Of course it is not a difficult thing because there are many corner references read from various schools which are shared via social media accounts, talking about funds is certainly not a significant obstacle because you can utilize used items by processing them into new and unique objects that can be used as decoration in the corner of the room as a divider that marks a reading corner in the classroom.